2019
DOI: 10.21109/kesmas.v14i2.3111
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Practices, and Health Beliefs of Pregnant Women about Urinary Tract Infection and Its Associated Risk Factors: A Local Filipino Community Experience

Abstract: Urinary tract infection (UTI) during pregnancy is assumed to be associated with increased maternal and fetal morbidity and mortality; hence, a proper assessment of knowledge and practices is crucial to formulate preventive strategies to ensure the health of both the mother and the baby. The study determined the knowledge, attitude, practices (KAP), and the beliefs of pregnant women about UTI based on the Health Belief Model. A survey questionnaire was used to gather data from pregnant women with and without UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
(8 reference statements)
2
7
0
1
Order By: Relevance
“…Furthermore, even though education can significantly reduce UTI recurrence and complications, financial constraints could negatively influence knowledge due to unsatisfactory educational attainment. 27 For instance, this report found that unemployed parents had lower total awareness scores than retired or employed parents. 27 …”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Furthermore, even though education can significantly reduce UTI recurrence and complications, financial constraints could negatively influence knowledge due to unsatisfactory educational attainment. 27 For instance, this report found that unemployed parents had lower total awareness scores than retired or employed parents. 27 …”
Section: Discussionmentioning
confidence: 83%
“… 27 For instance, this report found that unemployed parents had lower total awareness scores than retired or employed parents. 27 …”
Section: Discussionmentioning
confidence: 83%
“…These findings were in agreement with a study in Egypt conducted by Mohamed H et al, (2019) (43) who revealed that most of the adolescent students had poor knowledge regarding UTI. Another study in Filipino by Navarro et al, (2019) (44) concluded that the majority of the respondents had unsatisfactory knowledge of UTI. The studies of Khanal et al, (2014) (45 ) and El Lawindi et al,(2015) (34) also support ourfindings.…”
Section: Resultsmentioning
confidence: 98%
“…Individuals with a high level of self-efficacy are also more likely to begin self-care activities, persevere in the face of adversity, and master new practices. In this context, Navarro et al (2019) discovered that self-efficacy is a primary mediator of the association between knowledge and practice. As a result, increasing selfefficacy regarding urinary tract infections during pregnancy requires special attention.…”
Section: Introductionmentioning
confidence: 99%
“…The motivation for this research and its significance stems from several existing studies. First, Navarro et al (2019) argued that pregnant women with urinary tract infections should learn about self-care practices related to the self-efficacy nursing guidelines to decrease symptoms and improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%